2019
DOI: 10.2147/ptt.s154073
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spotlight on itolizumab in the treatment of psoriasis – current perspectives from India</p>

Abstract: Psoriasis is a chronic, debilitating, immune-mediated, systemic inflammatory disease affecting mainly skin, nails, and joints. Several therapeutic modalities are available depending on the severity of the disease. Long-term use of these drugs results in unwanted effects and toxicities. Recently, itolizumab, a humanized monoclonal immunoglobulin G1 antibody to CD6, has shown appreciable clinical effects and safety profile in patients with moderate-to-severe chronic plaque psoriasis. A literature search was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Repurposing of anti-inflammatory biologics such as Itolizumab could play an important role in treating the cytokine storm and complications due to COVID-19 infection and reduce mortality due to cytokine storm complications. Itolizumab is an approved drug in India for psoriasis with a proven safety profile [19][20][21]25] and has been used in a clinical trial for treating COVID-19 complications. Itolizumab is being used for compassionate treatment of patients with moderate to severe ARDS due to COVID-19 at several hospitals in India.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Repurposing of anti-inflammatory biologics such as Itolizumab could play an important role in treating the cytokine storm and complications due to COVID-19 infection and reduce mortality due to cytokine storm complications. Itolizumab is an approved drug in India for psoriasis with a proven safety profile [19][20][21]25] and has been used in a clinical trial for treating COVID-19 complications. Itolizumab is being used for compassionate treatment of patients with moderate to severe ARDS due to COVID-19 at several hospitals in India.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Several clinical studies have demonstrated the efficacy of itolizumab, a humanized monoclonal antibody that selectively targets CD6, in the systemic treatment of moderate-to-severe psoriasis ( 64 66 ). Itolizumab binds to domain 1 of CD6 and inhibits T cell activation, proliferation, and secretion of proinflammatory cytokines involved in the pathogenesis of psoriasis ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soon after, the mouse 12.1 mAb was used as an immunosuppressive agent in human kidney and bone marrow transplantation to prevent acute rejection based on its T-cell-depleting cytotoxic properties [52,53] (Table 1). Subsequently, the original mouse version (IOR-T1) of itolizumab, a humanised mAb against human CD6 currently approved for the treatment of psoriasis [54] (Table 1), was assayed for topical treatment of cutaneous T-cell lymphoma (CTCL) skin lesions [55] (Table 1). The humanised version of the non-depleting mouse anti-human CD6 UMCD6 mAb previously tested in experimental mouse models of autoimmune encephalitis and arthritis [30,66] has recently been tested in pre-clinical models of human T-cell lymphoma (TCL) [57] (Table 1).…”
Section: Depleting and Non-depleting Anti-cd6 Mab-based Strategiesmentioning
confidence: 99%